EKPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY DENGAN METODE PROBLEM SOLVING PADA POKOK BAHASAN PERSAMAAN GARIS LURUS DITINJAU DARI KATEGORI MULTIPLE INTELLIGENCES PESERTA DIDIK KELAS VIII SMP NEGERI DI KABUPATEN KARANGANYAR - Fitriawan, Dona (Jurnal Pembelajaran Matematika, 2013)
Abstract: The aims of the research were to determine the effect of learning models onlearning achievement viewed from students’ multiple intelligences. The learning models compared werecooperative learning model Two Stay Two Stray (TSTS) with problem solving method, Two Stay TwoStray (TSTS) and conventional. This research was a quasi-experimental research using 3?3 factorialdesign. The populations of the research were all students of Junior High School (SMP) onKaranganyar Regency. The samples of the research were the eight grade students of SMP Negeri 1Tasikmadu, SMP Negeri 2 Jaten, and SMP Negeri 5 Karanganyar containing 282 students (94students for first experimental class, 93 students for second experimental class, and 95 students forcontrol class). The samples were chosen by using stratified cluster random sampling. In collectingthe data, the instruments used were test and questionnaire. Test was used to get the students’learning achievement data and questionnaire was used to get multiple intelligences data. Thetechnique of analyzing the data was unbalanced two-ways Anova. The result of the research showsthat: (1) TSTS with problem solving method is better than TSTS and conventional in producingthe students’ Mathematics learning achievement, meanwhile TSTS is as good as conventional inproducing students’ Mathematics learning achievement; (2) students having high multipleintelligences are better than those having middle and low multiple intelligences in producing thestudents’ Mathematics learning achievement, meanwhile students having middle multipleintelligences are better than those who have low multiple intelligences in producing Mathematicslearning achievement; (3) (a) the students’ having high multiple intelligences taught by usingTSTS with problem solving method are better than those having middle or low multipleintelligences in producing the students’ Mathematics learning achievement whereas studentshaving middle multiple intelligences have better learning achievement than those who have lowmultiple intelligences; (b) The students’ having high multiple intelligences taught by using TSTSare better than those who have low multiple intelligences in producing the students’ Mathematicslearning achievement but the students having high multiple intelligences taught by using TSTS areas good as those who have middle multiple intelligences; (c) The students taught by usingconventional having high, middle or low multiple intelligences produce same learningachievement; (4) (a) the students having high multiple intelligences taught by using TSTS withproblem solving method are as good as who are taught by using TSTS and conventional inproducing students’ Mathematics learning achievement; (b) the students having middle multipleintelligences taught by using TSTS with problem solving method are better than those who aretaught by using TSTS and conventional in producing students’ mathematics learning achievementbut they are as good as those who are taught by using TSTS whereas the students taught by usingTSTS are as good as those who taught by using conventional; (c) the students having low multipleintelligences taught by using TSTS with problem solving method, TSTS, and conventional havethe same mathematics learning achievement.Keywords : TSTS, problem solving, multiple intelligences